ALGORITHMIC PEDAGOGY IN ISLAMIC EDUCATION: THE SHIFT FROM SANAD AUTHORITY TO DIGITAL METRICS - Anisatun Muthi’ah; Muhammad Faiq Hammam; Ahmed Abdul Malik; Asyifa Nadia Jasmine; Rachma Fadhila Usman (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed how the logic of ‘Algorithmic Pedagogy’ operates to disrupt sanad-based religious authority and alter the epistemic structure of Islamic education. Employing a qualitative digital inquiry approach, the unit of analysis encompasses popular digital da’wah channels, specifically on YouTube and Instagram. The criteria for selecting content and accounts were based on high visibility, follower influence, and platform representation. Data collection was conducted through non-participatory digital observation over a six-week period, from June 11 to July 20, 2025. Utilizing the concept of ‘Algorithmic Pedagogy’ for data analysis, the findings reveal that this logic operates within Islamic education through three primary mechanisms: (1) Epistemic Displacement, wherein legitimacy shifts from scholarly credentials to digital engagement metrics; (2) Affective Distillation, which reduces complex theological teachings into shallow, emotionally charged commodities; and (3) Structural Polarization, wherein algorithms amplify extreme narratives over moderate traditions to maximize user retention. This study argued that this pedagogical shift engenders a new regime of truth that privileges visual performativity over scholarly authenticity. Ultimately, this research underscored the urgent need for formal Islamic educational institutions to integrate critical algorithmic literacy into their curricula, thereby equipping the younger generation to counter digital polarization and affective manipulation.